Evaluasi Implementasi Program Sanitasi Berbasis Masyarakat di Jawa Tengah dan Jawa Timur - Sidjabat, Filson M; Gunawan, Michelle (Al-Ard: Jurnal Teknik Lingkungan, 2020)
Goal 6 of the SDGs has a target for clean water and sanitation, by 2030 the UN has a target of providing universal access to sanitation. Safely managed sanitation can support the progress to supporting socioeconomic development and promoting equality. In developing countries, a majority of the general population does not have access to proper sanitation. Therefore, there are still many challenges faced for sanitation in developing country. Unmanaged sanitation has a negative impact to human health and the environment. In developing countries that has a lot of under developed and rural area, community-based sanitation program is one of the approach for educating and improving sanitation. This study has an objective to evaluate the current implementation of community-based sanitation programs in Indonesia. This study is a literature review that analyzed various sources in a systematical way to evaluate the implementation of community based sanitation programs in Indonesia. In conclusion, the implementation of community based sanitation programs yield a positive impact for the targeted community. The factors that has influence are community involvement, funding and enforcement of sanctions.